2021
DOI: 10.1155/2021/1978111
|View full text |Cite
|
Sign up to set email alerts
|

Remote Facial Expression and Heart Rate Measurements to Assess Human Reactions in Glass Structures

Abstract: In engineering applications, human comfort fulfillment is challenging because it depends on several aspects that can be mathematically controlled and optimized, like in case of structural, energy, or thermal issues, and others. Major troubles can indeed derive from combined human reactions, which are related to a multitude of aspects. The so-called “emotional architecture” and its nervous feelings are part of the issue. The interaction of objective and subjective parameters can thus make the “optimal” building… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 36 publications
(33 reference statements)
0
8
0
Order By: Relevance
“…Out of the 147 empirical studies included, only five papers were studies on how building monolithic elements brings about emotional changes in subjects. These were studies of building distribution forms, block aspect ratios [38] and building elevations [46,53,55,144]. These studies give designers an empirical basis for understanding which building monolithic designs are preferred by users.…”
Section: Building Facadementioning
confidence: 99%
See 1 more Smart Citation
“…Out of the 147 empirical studies included, only five papers were studies on how building monolithic elements brings about emotional changes in subjects. These were studies of building distribution forms, block aspect ratios [38] and building elevations [46,53,55,144]. These studies give designers an empirical basis for understanding which building monolithic designs are preferred by users.…”
Section: Building Facadementioning
confidence: 99%
“…Ningning Ding et al asked subjects to view photos of plants in different living environments, and explored people's visual preferences for plant features in different living environments by analyzing subjects' eye-tracking and EEG [151]. Nubani Linda et al analyzed the impact of virtual tours on viewers, using facial expression recognition software to record and analyze participants' emotional responses during their experience of a cyber museum [53]. It was found that when a significant percentage of architectural details, spatial transitions, and product details are captured during the construction of a cybermuseum, which may be just as engaging as visiting the museum in person.…”
Section: D Multimedia Environmentmentioning
confidence: 99%
“…This interaction may result from multiple reasons such as, for example, the aesthetic impact of a construction (and thus emotions [9][10][11]), or the sensitivity to human motion (such as in terms of perceived vibrations [12,13]), and the subjective reaction of humans to structural responses. This is particularly relevant when "emotional architectures" are the context of human activities [9][10][11], and in those configurations, glass material has a primary emotional effect on humans, for many reasons [12][13][14][15]. According to Figure 1, wearable sensors able to capture specific biometric parameters of customers can thus play a key role in the quantitative measure of human reactions [14,15].…”
Section: Sensors For Human-comfort-driven Structural Designmentioning
confidence: 99%
“…Psychological effects affect user satisfaction. Similarly, learning psychology impacts the curriculum, positively or negatively [12,13]. However, a series of deep-seated problems are exposed in the process of the implementation of the existing curriculum; for example, the curriculum fails to meet the learning psychological needs of students, and the curriculum evaluation system overlooks the complex relationship impacting the indexes, among others [14].…”
Section: Introductionmentioning
confidence: 99%